Sistem Kontrol Kadar Amonia Dan Tinggi Air Pada Kolam Penangkaran Tukik Penyu - Pitos Hababil, Riego; Rahmadya, Budi (Universitas Andalas, 2024)
Turtles are also one of the animals whose population is decreasing day by daydue to several factors ranging from climate change, disease, environmentaldamage and inadequate processing of conservation techniques and so on. Withthe status of turtles being endangered, special attention is needed for turtles inthe form of cultivating turtles, especially when the turtles are still 0-2 years oldor known as hatchlings. One of the important indicators in hatchling cultivationrequires good seawater quality management. One of the parameters of goodseawater quality is ammonia levels. This ammonia level can be formed naturallyby metabolic wastes and also food waste that decomposes in the water whichresults in the formation of ammonia levels. In turtle hatchling ponds it is alsonecessary to adjust the water level in the pond with a height of 5cm - 10cmbecause newborn hatchlings cannot dive. The importance of regular waterquality control such as ammonia levels and water level in ponds is veryimportant for the success of hatchling cultivation. Therefore, a research onmonitoring and controlling systems for ammonia levels and water levels usingthe TCS3200 color sensor is carried out to read the change in water color afteradministration of an ammonia test solution which will show the value ofammonia levels in water. Previously, water sampling was carried out by DCpumps and ultrasonic sensors to detect water level. Where this system canmonitor and control ammonia levels and height automatically and the resultscan be viewed using a smartphone through the Blynk application